Closed-form solution for predicting tensile strength and fracture toughness of ultra-high-performance concrete. (February 2023) - Yang, Shutong; Sun, Zhongke; Wang, Junhao; Yang, Tiange; Ren, Zhenhua; Lan, Tian
Abstract: As a popular cementitious material in civil engineering in recent years, ultra-high-performance concrete (UHPC) has been used in harsh working conditions for its superior mechanical properties and durability. However, cracking in UHPC is a significant threat to its durability. Thus, studying the fracture properties of UHPC for rational design of crack resistance is important. The aim of this study was to develop closed-form solutions of the size-independent tensile strength ( f t ) and fracture toughness ( K IC ) of UHPC. Three-point-bending tests were performed on 80 UHPC beams with different depths and initial crack lengths; the fracture behaviour was comprehensively analysed and a predictive model was proposed to determine f t and K IC . A characteristic microstructure parameter ( C ch ) and two discrete coefficients ( β and C ) were introduced to indicate material heterogeneity and discontinuity, respectively. C ch was determined as the average fibre spacing in this study. These coefficients also quantified the critical effective crack propagation length at the maximum fracture load ( F max ) and the characteristic crack length defined by the bulk toughness and strength properties. A linear relationship of F max with respect to f t and K IC was established; the size-independent f t and K IC were obtained after determining F max from three-point-bending tests. The effects of C ch, β, and C on the predicted f t and K IC values were analysed. Although both f t and K IC exhibited certain differences as C ch, β and C were simultaneously varied, the results were within the upper and lower limits of the f t and K IC values predicted by statistical analysis. Highlights: Fracture mechanism of UHPC was comprehensively analyzed and clarified. Characteristic microstructure parameter was correlated to fiber characterization. Critical crack propagation length at maximum load was discretized quantitatively. Maximum load was linked to tensile strength and fracture toughness linearly. Scatters in the predicted results were analyzed based on a statistical analysis.